ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN DAN PENILAIAN KINERJA TERHADAP KINERJA DENGAN MEDIASI MOTIVASI (Studi pada Pegawai Kantor Balai Pelatihan Kesehatan (Bapelkes) Semarang) - Nur Yatiman, 1342020007 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this current research is to examine the effect of job characteristics and performance appraisal on motivation and employee performance. In addition, the research aims to know the role of motivation in mediating the relationship between job characteristics and performance appraisal on employee performance. Data analysis using regression analysis and mediated effect analysis. Result concluded that only job characteristics that has not significant effect on employee performance. Furthermore, result also proved that motivation has a mediating role in influencing the relationship between job characteristics and employee performance, but not for the relationship between performance appraisal and employee performance. Based on research results, efforts to increase employee performance through job characteristics cannot ignore the motivation aspect. The results implied that performance appraisal was faster to improve the employee perfomance than job characteristics. Keywords: Job Characteristics, Performance Appraisal, Motivation, and Employee Performance